Clinical Utility of Next-generation Sequencing in the Management of Myeloproliferative Neoplasms: A Single-Center Experience. Issue 3 (June 2018) - Alduaij, Waleed; McNamara, Caroline J.; Schuh, Andre; Arruda, Andrea; Sukhai, Mahadeo; Kanwar, Nisha; Thomas, Mariam; Spiegel, Jay; Kennedy, James A.; Stockley, Tracy; Tsui, Hubert; Devlin, Rebecca; et al.
Abstract : Abstract: Although next-generation sequencing (NGS) has helped characterize the complex genomic landscape of myeloid malignancies, its clinical utility remains undefined. This has resulted in variable funding for NGS testing, limiting its accessibility. At our center, targeted sequencing (TAR-SEQ) using a 54-gene NGS myeloid panel is offered to all new patients referred for myeloid malignancies, as part of a prospective observational study. Here, we evaluated the diagnostic, prognostic, and potential therapeutic utility of clinical grade TAR-SEQ in the routine workflow of 179 patients with myeloproliferative neoplasms (MPN). Of 13 patients with triple negative (TN) MPN, who lacked driver mutations in JAK2, CALR, and MPL, TAR-SEQ confirmed clonal hematopoiesis in 8 patients. In patients with intermediate-risk myelofibrosis (MF), TAR-SEQ helped optimize clinical decisions in hematopoietic cell transplant (HCT)-eligible patients through identifying a high molecular risk (HMR) mutation profile. The presence of an HMR profile favored HCT in 9 patients with intermediate-1 risk MF. Absence of an HMR profile resulted in a delayed HCT strategy in 10 patients with intermediate-2 risk MF, 7 of which were stable at the last follow-up. Finally, TAR-SEQ identified patients with various targetable mutations in IDH1/2 (4%), spliceosome genes (28%), and EZH2 (7%). Some of these patients can be potential candidates for future targeted therapy trials. In conclusion, we have demonstrated that TAR-SEQ improves the characterization of TN MPN, can be integrated in clinical practice as an additional tool to refine decision making in HCT, and has the potential to identify candidates for future targeted therapy trials. Abstract : Supplemental Digital Content is available in the text